2007
DOI: 10.1016/j.ejvs.2007.05.006
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Volume and Outcome Following Elective Open Repair of Abdominal Aortic Aneurysms (AAA) in 131 German Hospitals

Abstract: Patient's age, ASA classification, AAA diameter, length of procedure, suprarenal clamping and blood transfusion are predictive variables for an increased perioperative mortality in elective open AAA repair. Mortality is also increased by a low annual volume. Further studies are needed to examine whether these data are applicable to all German hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…only one study (17) had the explicit aim of searching for the best thresholdvalue to separate volume-mortality groups. Most of the studies demonstrated as ignificant inverse volume-mortality relationship but the heterogeneity of study design makes it difficult to pool results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…only one study (17) had the explicit aim of searching for the best thresholdvalue to separate volume-mortality groups. Most of the studies demonstrated as ignificant inverse volume-mortality relationship but the heterogeneity of study design makes it difficult to pool results.…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen other papers (model studies, studies on the effect of surgeon volume or specialization and others) werealso excluded. Thus 15 papers weret he base of the present study.T welve papers originated in north America (USA , Canada (15,16)) and three in Europe (UK (15,16),Germany (17)). reference lists provided one morerelevant US article (12).…”
Section: Method Materialsmentioning
confidence: 99%
“…In reverse, a meta-analysis considering 115,273 elective open AAA repairs mentioned a mean mortality rate of 5.56 %, with a significant relationship between higher surgeon caseload and lower mortality (E.L. Young et al, 2007). After all, the German national registry comprising 10,163 elective open repairs of AAA performed in 131 hospitals reported an overall perioperative mortality rate of 3.2% (Eckstein et al, 2007).…”
Section: Perioperative Mortality After Endovascular and Open Repair Omentioning
confidence: 99%
“…Recent publications distinguish between patients with an open and an endovascular aneurysm repair (EVAR) (Dimick and Upchurch, 2008;Holt et al, 2009;Landon et al, 2010;McPhee et al, 2011). So far, evidence for Germany is lacking with only one study from Eckstein et al (2007). They used clinical data from the Hip fracture is less frequently evaluated in volume-outcome studies.…”
Section: Introductionmentioning
confidence: 99%
“…The authors used data from 1993 to 1998 with a total of 26,005 patients and found significant differences in mortality rates between patients treated in hospitals with the lowest case volume and patients treated in hospitals with the highest case volume. But like Eckstein et al (2007) the cluster structure of the data was not considered and no further hospital characteristics were added to the regression analysis.…”
Section: Introductionmentioning
confidence: 99%